Why humans have cultures : explaining anthropology and social diversity - Carrithers, Michael (Oxford ; New York : Oxford University Press, 1992)
1. Antrophology 2. Culture 3. Social evolution
Includes bibliographical references and index.
Faculty
Keywords: Anthropology; Culture; Social evolution